PENGARUH KEPUASAN KERJA, KOMPENSASI DAN ORGANIZATIONAL CITIZENSHIP BEHAVIOUR (OCB) TERHADAP KINERJA KARYAWAN PADA PT CENDANA HAN WIJAYA - Wu, Vannisa; Nainggolan, Nora Pitri (LPPM Universitas Putera Batam, 2021)
Judging from the tightness of competitive era in this time, a company in order to carry out it is activities tries to fulfill the needs in achieving the targets that have been planned and increasing the companies competition to strengthen the continuity of thecompanies. In order to achieve the company’s goals in improving employee performance by monitoring job satisfaction, compensation commensurating and improving Organizational Citizenship Behaviour (OCB), the company undertook various ways. The researcher used a saturated sampling technique where the data tested comes from all members of the population with result of 110 respondents. The information were collected by doing SPSS version 20. The result of f-test research indicate that job satisfaction, compensation and Organizational Citizenship Behaviour (OCB) together have a significant effect on employee performance whichf-count > f-table (40,389 > 2,69) with a sigficant value < 0,05.